WOMEN IN PRISON – MOTHER WITH CHILDREN. EXPERIENCES OF THE CZECH REPUBLIC. OUTLINE OF THE PROBLEM - Jana FIRSTOVÁ (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The paper presents the issue of imprisonment of women with minor children. The text is contemporary (in outline) and presents the reality behind functioning of units of the Czech penitentiary system, in which the inmates are, pursuant to a final judgment of conviction, mothers with their minor children.